Conceptualizing and measuring autocratization episodes - Lott, Lars; Croissant, Aurel (Swiss political science review, 2021)
Autocratization affects democracies and autocracies with gradual setbacks in democratic qualities. The current debate on autocratization is lacking a comprehensive and systematic overview of different autocratization concepts and empirical measures. Addressing the gap, this research note identifies and discusses different strategies of operationalizing autocratization periods with continuous democracy data from Freedom House, Polity IV and the Varieties of Democracy (V-Dem) project. Evidence for 26 different autocratization measures for 1900-2019 reveals major inconsistencies between different measures. Our findings suggest that autocratization episodes should be measured with V-Dem’s Electoral Democracy Index (EDI) or with V-Dem’s Liberal Democracy Index (LDI), which provide fine-grained data and the possibility to test for measurement noise. A 10% threshold reduces the risk of conceptual stretching and enables researchers to detect both autocratization episodes that do and do not result in regime breakdown. We also recommend researchers to additionally test empirical findings with different carefully selected threshold